On double phase Kirchhoff problems with singular nonlinearity - Arora, Rakesh; Fiscella, Alessio; Mukherjee, Tuhina; Winkert, Patrick (De Gruyter Open Ltd, 2023)
In this paper, we study multiplicity results for double phase problems of Kirchhoff type with right-hand sides that include a parametric singular term and a nonlinear term of subcritical growth. Under very general assumptions on the data, we prove the existence of at least two weak solutions that have different energy sign. Our treatment is based on the fibering method in form of the Nehari manifold. We point out that we cover both the nondegenerate as well as the degenerate Kirchhoff case in our setting.
This paper published with affiliation IIT (BHU), Varanasi in Open Access Mode.
Keywords: double phase operator; fibering method; Kirchhoff term; multiple solutions; Nehari manifold; singular problems